1996
DOI: 10.1177/009286159603000414
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey of Hospital Adverse Drug Event Monitoring and Reporting Systems

Abstract: The purpose of this research was to collect information concerning the systems which hospitals have developed to monitor and report adverse drug events (ADE). In addition, the attitudes and perceptions of those coordinating the program toward postmarketing surveillance of such events were investigated. The sample was stratified by hospital size. Questionnaires were sent to 725 Joint Commission for Accreditation of Health Care Organization accredited hospitals (30.5 small, 27.5 medium, and 14.5 large). Complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…However, a national survey of adverse drug reaction monitoring systems found that the ratio of nurses' reports to physicians' reports varied with the size of the hospital. 31 Institutions should use whatever source is best in their setting to detect, report, and reduce ADEs.…”
Section: Discussionmentioning
confidence: 99%
“…However, a national survey of adverse drug reaction monitoring systems found that the ratio of nurses' reports to physicians' reports varied with the size of the hospital. 31 Institutions should use whatever source is best in their setting to detect, report, and reduce ADEs.…”
Section: Discussionmentioning
confidence: 99%
“…5 A larger percentage of the population is seen in the ambulatory care setting than in hospitals or nursing homes.Although there are several published models describing ADR programs in the hospital setting, very few have addressed programs applicable to the ambulatory setting. 6,7 This deficiency in the literature may be secondary to the standards developed by the Joint Commission for Accreditation of Healthcare Organizations, which mandates a mechanism to identify and report ADRs in hospitals. This standard does not explicitly require ADR reporting in the ambulatory setting.…”
mentioning
confidence: 99%